IDENTlFIKASI FAUNA DI KAWASAN EKSPLORASI LNG-BP BABO-BINTUNI PAPUA BARAT - Wajo, Muhamad Jen (Fakultas Peternakan Universitas Papua, 2010)
The research was conducted in the area of Tangguh LNG exploration at Babo-Bintuni on February-June 2002. Observations ware done at the 9 (nine) points done intentionally. Estimation of population and density using the Hanson method was applied. The observation results showed that the number of the most widely fauna found in the region was from avifauna that i.e. 16 species with a frequency of density was between 0.4 to 49.9. The largest population was dominated by marine birds, i.e. storks (Egreta Intermedia) and gull (Malurus Cyanocephalus) that accupy mangrove cover as a place to grow. Mammals found ware deer (Cervus timorensisi), wild boar (Sus scrofa) and possum (Phalanger, sp). Small reptiles found monitorlizard (Varanus salvator) and several species of snakes.